Pomegranate (Punica granatum L.) leaf analysis: Correlation with harvest - Giménez M.; Martínez J.; Oltra M.A.; Martínez J.J.; Ferrández M. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
In the following work an exhaustive analysis is made of the knowledge of pomegranate (Punica granatum L.) leaf levels and their correlation with harvest in order to establish corresponding standard ranks. The following elements have been studied: nitrogen, phosphorus, potassium, calcium, magnesium, iron, zinc, manganese, copper, boron, and sodium. The leaf analysis technique has been used in order to determine the contents of such elements. The variety studied was a clone selection belonging to the population variety Mollar (MC1). This variety is one of those most commonly grown in the south-east of Spain, as well as another well-known Israeli early variety.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)